ALCOHOL USE IN A GROUP OF ADOLESCENTS AS SOCIALLY DEFINED DEVIANT BEHAVIOR - Saukuma, Ieva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Alcohol consumption among adolescents in social theories is considered a formally defined deviant behavior. There is no doubt about the negative health consequences of this behavior, however, several researchers point to its role in the process of growing up and socialization. Along with the development of theories of deviant behavior, the question – whether alcohol consumption among adolescents is still identified as deviant behavior, becomes relevant. To assess the aspect of alcohol consumption as a socially determined deviance, the results of a longitudinal cohort study among Latvian schoolchildren were analyzed. The analysis of the research data includes such indicators as the characteristics of the situation and age of the adolescent when they try to alcohol first and the attitude of parents towards adolescents alcohol use. The research data were compared in four stages from the start of 7th grade (T1) till the end of 9th grade (T4). The results indicate that adolescents are well informed about the legal ban on alcohol consumption (at the beginning of the study in the T1 period, 89.3% were aware of the ban on the use of alcohol by minors). Still, the contradictory behavior of the parents, allowing adolescents to consume alcohol (in the T4 period, 65.9% of students who have consumed alcohol, their parents have permitted to do so) creates an ambiguous perception of alcohol consumption as a deviant behavior among adolescents. In general, this contradiction can reduce the effectiveness of normative and communicative tools in the prevention of alcohol initiation among adolescents. The results of the study confirm - that to delay the initiation of alcohol consumption among adolescents - it is necessary to define alcohol consumption among adolescents as deviant behavior in society as a whole.